Sarcomatoid renal pelvis carcinoma: A case report - Xuechao Zhang; Yanan Jin; Weiran Zhang; Yawei Zhang; Haifeng Wang (Urology Case Reports)
Sarcomatoid carcinoma is a malignant tumor of epithelial origin, some of the cells of which are differentiated in a sarcomatoid direction and are highly invasive. Sarcomatoid renal pelvis carcinoma (SRPC) is very rare. This article reports on an elderly woman with SRPC and discusses the clinical and pathological features and prognosis of SRPC in the hope of providing a reference for the diagnosis and treatment of this disease.